Enhancement of lentiviral vector production through alteration of virus-cell interactions - Gelinas, J (2016)
Gene therapy is the introduction or alteration of genetic material with the intention to treat disease. To support this aim, viruses have been modified, with elements linked to viral pathogenicity removed from their genome and replaced by the genetic material to be delivered. Gene therapy vectors based on lentiviruses have many advantages, such as the ability to transduce non-dividing cells and to target specific cell types via pseudotyping. They have been successfully used in ex vivo clinical trials for several haematopoietic stem cell disorders. Lentiviral vectors, however, suffer from substantially lower titres than the more popular adeno-associated virus (AAV)-based vectors and therefore have limited applicability for in vivo gene therapy which requires much greater quantities of virus. The main aim of this thesis was to investigate strategies to improve lentiviral vector productivity during manufacture, in order to increase the likelihood of lentiviruses being adopted for disease treatment. Initial experiments were based on the lentiviral vector manufacturing process currently being developed by the United Kingdom Cystic Fibrosis Gene Therapy Consortium for the generation of highly concentrated, purified lentivirus for clinical use. Supplementation of FreeStyle 293 Expression Medium used during upstream processing was attempted, but none of the assessed supplements led to significant increases in lentiviral vector production. Investigation into intrinsic immunity to viral infection indicated that over-expression of the protein kinase RNA-activated (PKR) led to lower production titres, but over-expression of its inhibitors was not successful at increasing titres. The focus then shifted to reducing, or 'knocking-down', inhibitory factors present in the host cells, which could adversely affect viral titres. Investigation of the published HIV-1 literature revealed a possible 152 candidate inhibitory factors described as having a negative impact on HIV-1 replication in the late stages of the life cycle of the virus. A novel siRNA screen was developed to assess the effect of ‘knock-down’ of inhibitory factors on lentiviral vector titre. Application of the screen to 89 candidate inhibitory factors identified nine genes which, when knocked-down, resulted in increased lentiviral vector production by more than 40%. Further work will be necessary to understand the role of the inhibitory factors in lentiviral vector production, but novel cell lines in which genes encoding these factors have been permanently deleted from producer cells could lead to higher titres, reducing costs in the manufacture of lentiviral vectors and making in vivo gene therapy more feasible from a health economics perspective.